Psychiatric Disorders Complications in HIV/AIDS Patients and the Factors Influencing Them at the Karawang District General Hospital - Purba, Evani; Gunawan, Fizal; Maduma, Ceyka; Tantular, Gabriella; Gunawan, Arif (Syntax Corporation Indonesia, 2025)
HIV infection increases a patient's risk of developing various psychiatric disorders, including depression, mania, psychosis, post-traumatic stress disorder (PTSD), and substance abuse. In addition, antiretroviral therapy (ART) may trigger or exacerbate psychiatric symptoms, potentially affecting treatment adherence and overall quality of life. This study aimed to identify the prevalence of psychiatric disorder complications among HIV/AIDS patients and to analyze the factors influencing their occurrence at Karawang District General Hospital. A cross-sectional study design was employed using data obtained from medical records and patient interviews at the HIV alternative polyclinic of Karawang District General Hospital in August 2025. The target population consisted of 300 patients who met the inclusion and exclusion criteria. Data collection instruments included the Self-Reporting Questionnaire (SRQ-29) and structured medical interviews. Statistical analysis was performed using SPSS with multinomial regression and binary logistic regression methods. The results showed that 54.3% of patients did not experience psychiatric disorders, while 45.7% had at least one type of psychiatric disorder. Among those with psychiatric disorders, PTSD symptoms were the most prevalent (45.3%), followed by organic mental disorders (27.8%), psychotic disorders (23.3%), and substance abuse disorders (3.7%). The use of Atripla (efavirenz, emtricitabine, and tenofovir) increased the risk of psychiatric symptoms by 1.518 times, although this association was not statistically significant. Overall, the findings indicate a considerable burden of psychiatric symptoms among HIV/AIDS patients, highlighting the need for integrated mental health screening and management in HIV care.